The correlation of HLA-A in Thai EGFR-mutated advanced non-small cell lung cancer, outcome, and tumor microenvironment - Nicha Zungsontiporn; Korakot Srianuwattipong; Sakun Santisukwongchote; Piyada Sitthideatphaiboon; Poonchavist Chantranuwat; Chatchawit Aporntewan; Chanida Vinayanuwattikun (Scientific Reports)
Abstract Previously reported HLA class I correlated with the outcome of early-stage non-small cell lung cancer (NSCLC) in the Japanese population. The binding affinity capability of the EGFR mutation peptide and various HLA-A subtypes could explain this. We conducted a prospective cohort study to explore advanced EGFR-mutated NSCLC patients who received EGFR TKIs in various HLA-A subtypes, the outcomes of treatment, and tumor immune microenvironment (TIME). Eighty-four advanced NSCLC harboring EGFR exon 19 deletion and exon 21 L858R mutations were analyzed. Among these, the interested HLA-A subtypes of exon 19 deletion were composed of HLA-A*03:01 (7.1%), *30:01 (3.7%),*11:01 (82.1%), and *68:01 (7.1%). The interested HLA-A subtypes of exon 21 L858R were HLA-A*30:01 (28.5%), *33:03 (57.1%), and *34:01 (14.4%). Multivariate Cox-regression analysis revealed that the interested HLA-A subtypes were not an independent factor of progression-free or overall survival. No correlation was found between HLA-A subtypes and either inflammatory TIME or the presence of intra-tumoral CD8 TILs. HLA-A subtypes did not correlate with prognostic outcomes in sensitized EGFR mutations. The diverse binding affinity with EGFR peptides was not translated into the TIME patterns.